2018
DOI: 10.1186/s12871-018-0500-1
|View full text |Cite
|
Sign up to set email alerts
|

Prospective investigation of intravenous patient-controlled analgesia with hydromorphone or sufentanil: impact on mood, opioid adverse effects, and recovery

Abstract: BackgroundRadical surgery for colorectal cancer, associated with moderate to severe postoperative pain, needs multimodal analgesia with opioid for analgesia. Despite considerable advancements, the psychological implications and other side effects with opioid remain substantially unresolved. This study aimed to investigate the impact on mood, side effects relative to opioid, and recovery of the patients with hydromorphone or sufentanil intravenous patient-controlled analgesia (IV-PCA) in a multimodal perioperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 33 publications
0
27
1
1
Order By: Relevance
“…As warming blankets were used the whole course, shivering didn't occur in the two groups. Pruritus didn't happen in either group, and that may be due to the morphine-free anesthetic method [27] in this study. As to the incidence rate of hypertension, hypotension, tachycardia, bradycardia, and PONV, differences were not significant, and it confirms that intraoperative DEX infusion during general anesthesia will not increase the incidence of postoperative adverse events.…”
Section: Discussionmentioning
confidence: 54%
“…As warming blankets were used the whole course, shivering didn't occur in the two groups. Pruritus didn't happen in either group, and that may be due to the morphine-free anesthetic method [27] in this study. As to the incidence rate of hypertension, hypotension, tachycardia, bradycardia, and PONV, differences were not significant, and it confirms that intraoperative DEX infusion during general anesthesia will not increase the incidence of postoperative adverse events.…”
Section: Discussionmentioning
confidence: 54%
“…Most studies have reported on the analgesic effects of hydromorphone and sufentanil and the incidence of adverse reactions in adults. Yanqing Yang et al showed hydromorphone and sufentanil had similar analgesic effects in adults undergoing elective laparoscopic or open radical surgery[ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, opioid receptors are distributed throughout the central and peripheral nervous systems, which means that opioid administration can induce effects beyond analgesia. The use of opioids even with PCA is associated with dose-dependent side effects, which limit their effectiveness in some patients [ 21 ]. To our excitement, in the current study, PG patients displayed less opioid consumption (morphine equivalent of 52.1 mg vs. 67.8 mg, P = 0.038) and fewer opioid-related side effects (11.8% vs. 25.0%, P = 0.036) than CG patients.…”
Section: Discussionmentioning
confidence: 99%